Subject global evaluation and subject satisfaction using injectable poly-L-lactic acid versus human collagen for the correction of nasolabial fold wrinkles - Brown, Spencer A; Rohrich, Rod J; Baumann, Leslie; Brandt, Fredric S; Fagien, Steven; Glazer, Scott; Kenkel, Jeffrey M; Lowe, Nicholas J; Monheit, Gary D; Narins, Rhoda S; Rendon, Marta I; Werschler, William Philip (Plastic and reconstructive surgery (1963), 2011)
This is a report of the secondary endpoints, Subject Global Evaluation (overall improvement) and Subject Satisfaction scores, from a study designed to examine the efficacy of injectable poly-L-lactic acid for the correction of nasolabial fold wrinkles over 25 months. A randomized, subject-blinded, parallel-group, multicenter clinical study was conducted to compare the effects of injectable poly-L-lactic acid with those of human collagen for the treatment of nasolabial fold wrinkles at 13 months following the last treatment. Injectable poly-L-lactic acid-treated subjects were followed for 25 months. From month 3 through month 13 following the last treatment, injectable poly-L-lactic acid-treated subjects (n = 116) reported significantly higher Subject Global Evaluation scores compared with human collagen-treated subjects (n = 117; p < 0.001). Overall Subject Global Evaluation scores for injectable poly-L-lactic acid-treated subjects were 99 percent at week 3, 91 percent at month 13, and 81 percent at month 25 (all times following the last treatment). In contrast, for human collagen-treated subjects, overall Subject Global Evaluation scores declined by 84 percent, from 96 percent at week 3 to 15 percent at month 13. Subject Satisfaction scores were significantly different (p < 0.01) between treatment groups beginning week 3 and continuing through month 13. Overall Subject Satisfaction scores were maintained for over 80 percent of injectable poly-l-lactic acid-treated subjects (n = 106) at month 25 after the last treatment. Treatment of nasolabial fold wrinkles with injectable poly-l-lactic acid resulted in statistically significantly higher Subject Global Evaluation and Subject Satisfaction scores compared with human collagen at 13 months. Injectable poly-l-lactic acid-treated subjects maintained improvements for up to 25 months after treatment.